THE INTEGRATION OF DIGITAL HUMANITIES (DH) IN BANGLADESHI LIBRARIES: PROSPECTS AND CHALLENGES - Rana, Md. Masud; Kabir, Shahjahan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study examines the role of Digital Humanities (DH) in the libraries of Bangladesh, with a focus on integrating digital technologies, staff training, and enhancing the accessibility of digital resources. Given the rapid advancement of digital tools in academic environments, this research aims to assess DH implementation in libraries, identify key challenges, and suggest strategies to enhance their effectiveness and inclusivity. The study adopts both quantitative and qualitative approaches. Data were collected through two primary methods: Google Forms and interviews, with a sample size of 103 respondents. The data collected were analyzed utilizing Structural Equation Modelling (SEM) with SmartPLS 4. The study finds a mixed adoption of digital humanities (DH) tools across libraries in Bangladesh, as the use of new technology required to fully digitalize them is still uneven. While urban academic libraries have made substantial progress in digitalizing resources and offering DH-based services, rural libraries continue to face significant barriers due to limited ICT infrastructure, the digital divide, and digital literacy gaps among staff and users. The analysis reveals that the lack of structured training for librarians and insufficient funding for infrastructure development pose significant obstacles. The study also highlights that integrating DH into libraries in Bangladesh is inevitable, as it can transform libraries into digital hubs for knowledge production and dissemination. The study recommends enhancing library ICT infrastructure, reducing the digital divide to make resources accessible to all, and offering digital literacy programs for both staff and library users.